Cloning, functional characterization, and co-expression studies of a novel aquaporin (FaPIP2;1) of strawberry fruit - Alleva, K. (2010)
In strawberry, the putative participation of aquaporins should be considered during fruit ripening. Furthermore, the availability of different firmness cultivars in this non-climacteric fruit is a very useful tool to determine their involvement in softening. In a previous work, the cloning of a strawberry fruit-specific aquaporin, FaPIP1;1, which showed an expression profile associated with fruit ripening was reported. Here, FaPIP2;1, an aquaporin subtype of PIP2 was cloned and its functional characterization in Xenopus oocytes determined. The FaPIP2;1 gene encodes a water channel with high water permeability (Pf) that is regulated by cytosolic pH. Interestingly, the co-expression of both FaPIP subtypes resulted in an enhancement of water permeability, showing Pf values that exceeds their individual contribution. The expression pattern of both aquaporin subtypes in two cultivars with contrasting fruit firmness showed that the firmer cultivar (Camarosa) has a higher accumulation of FaPIP1 and FaPIP2 mRNAs during fruit ripening when compared with the softer cultivar (Toyonoka). In conclusion, not only FaPIP aquaporins showed an expression pattern associated with fruit firmness but it was also shown that the enhancement of water transfer through the plasma membrane is coupled to the presence/absence of the co-expression of both subtypes. © 2010 The Author(s).